1993
DOI: 10.1038/ki.1993.100
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism, platelet intracellular free calcium and hypertension in chronic renal failure

Abstract: To investigate possible relationships between hyperparathyroidism, alterations in intracellular free calcium concentration ([Ca2+]i) and hypertension in chronic renal failure, serum concentrations of intact parathyroid hormone (PTH) were measured by two-site immunometric assay, and platelet ([Ca2+]i) was assessed using the fluorescent indicator fura-2. Thirty-six patients with chronic renal failure were studied, 10 with normal serum PTH concentrations (mean 8.0 +/- 0.6 pmol/liter), 17 with elevated serum PTH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 32 publications
0
46
0
2
Order By: Relevance
“…In a recent study using ambulatory blood pressure monitoring, the PTH level was the major determinant of blood pressure. 28 Moreover, recent observations linking the correction of hyperparathyroidism by either vitamin D administration 29 or parathyroidectomy 30 in chronic dialysis patients, resulting in a lower blood pressure, have supported this hypothesis. In our study, we found a correlation between PTH levels and predialysis MAP, but not PP.…”
mentioning
confidence: 55%
“…In a recent study using ambulatory blood pressure monitoring, the PTH level was the major determinant of blood pressure. 28 Moreover, recent observations linking the correction of hyperparathyroidism by either vitamin D administration 29 or parathyroidectomy 30 in chronic dialysis patients, resulting in a lower blood pressure, have supported this hypothesis. In our study, we found a correlation between PTH levels and predialysis MAP, but not PP.…”
mentioning
confidence: 55%
“…PTH excess in uremic patients has also been shown to increase cytosolic calcium levels that were correlated with the plasma PTH concentrations. These were also shown to be corrected with parathyroidectomy (PTX) (Raine, Bedford et al 1993). Even though increased calcium entry has been thought to be the most important step in sustaining high intra myocyte calcium concentrations reductions in the NA/K ATPase and Na/H exchange rates suggesting impaired calcium extrusion may contribute to altered cellular calcium homeostasis (Smogorzewski 1995).…”
Section: Uremic Cardiomyopathymentioning
confidence: 99%
“…The evidence based on a retrospective study in CKD patients demonstrating that systolic and diastolic blood pressure were significantly increased in subjects with increased plasma concentration of parathyroid hormone (PTH) [26]. Furthermore, a possible mechanism was suggested by the findings of increased platelet cytosolic calcium in the group with increased PTH plasma concentration.…”
Section: Pathophysiology Of Hypertension In Haemodialysis Patientsmentioning
confidence: 99%